EFEKTIVITAS CAMAT DALAM MENGOORDINASIKAN PENYELENGGARAAN PEMERINTAHAN DI KECAMATAN CILEUNYI KABUPATEN BANDUNG - Emmy, Emmy (Fakultas Politik Pemerintahan, 2018)
The coordination effectiveness of Camat in the implementation of government activities in Cileunyi sub-district is an important study especially in the context of synchronization, integration and synergicity of governing activities in Cileunyi Sub-district, Bandung Regency. This research uses qualitative research with descriptive method. Researcher used data collection techniques which are in-depth interviews, observation, and documentation. While the analysis and interpretation of data carried out by the process of analysis, there are data reduction, display data, and conclusion drawing. Results of study show that coordination of subdistrict head for the government activities in Cileunyi Sub-District, Bandung Regency in general, has been running well but not optimal. This is because of the lack of information and communication also the lack of utilization of information technology; and lack of coordination awareness. The coordination meeting on a regular basis is often attended by staff who is lack of the capacity, competence and authority in decision-making. The agreement and commitment for coordination is not optimal. The absence of a written agreement and commitment to coordinate each other. Also implementation of incentives or sanctions is not optimal, as well as feedback for the coordination process has not been utilized optimally and effectively by Cileunyi Sub-district Head. Various efforts have been made by Cileunyi Sub-district head in order to improve the coordination of governance in Cileunyi Sub-District, Bandung Regency, such as the creation of sub-district and village website; building discipline and responsibility for staffs in the performance of duties; raising coordination awareness and understanding; building relationships and work culture as a teamwork; forming a coordination forum; setting the agenda of coordination meetings on a regular basis; and building agreements and commitments to coordinate effectively.